Corporate Social Responsibility Initiatives Addressing Social Exclusion in Bangladesh - Werner, Wendy J (Journal of Health, Population and Nutrition, 2009)
The private sector is often seen as a driver of exclusionary processes rather than a partner in improving the health and welfare of socially-excluded populations. However, private-sector initiatives and partnerships- collectively labelled corporate social responsibility (CSR) initiatives-may be able to positively impact social status, earning potential, and access to services and resources for socially-excluded populations. This paper presents case studies of CSR projects in Bangladesh that are designed to reduce social exclusion among marginalized populations and explores whether CSR initiatives can increase economic and social capabilities to reduce exclusion. The examples provide snapshots of projects that (a) increase job-skills and employment opportunities for women, disabled women, and rehabilitated drug-users and (b) provide healthcare services to female workers and their communities. The CSR case studies cover a limited number of people but characteristics and practices replicable and scaleable across different industries, countries, and populations are identified. Common success factors from the case studies form the basis for recommendations to design and implement more CSR initiatives targeting socially-excluded groups. The analysis found that CSR has potential for positive and lasting impact on developing countries, especifically on socially excluded populations. However, there is a need for additional monitoring and critical evaluation. Key words: Corporate ethics; Corporate social responsibility; Employment; Income; Non-governmental organizations; Poverty; Rural population; Social exclusion; Bangladesh doi: 10.3329/jhpn.v27i4.3401 J Health Popul Nutr 2009 Aug;27(4):545-562